The Precarious Concept of Precarity. (September 2020) - Choonara, Joseph
This paper traces the roots of precarity as a concept emerging from French sociological discourse, then permeating through networks informed by Italian autonomism, before re-emerging in the writings of figures such as Guy Standing and Arne Kalleberg. It is shown that, despite the claims of the literature, precarity in employment is not typical in the United Kingdom. Here, temporary employment remains the exception and employment tenure remains stable. This can best be explained by radical political economy. Capital is not interested simply in engendering precarity; it is also concerned with the retention and reproduction of labor power, leading to contradictory imperatives. The resonance of the narrative of precarity, in spite of this, reflects a long retreat from class within radical theory and the insecurities present in working life.